ANALISA KEBIJAKAN PEMERINTAH PROVINSI DKI JAKARTA TAHUN 2017-2021 TERKAIT ANCAMAN PENGANGGURAN PASCA KENAIKAN INFLASI - Alex Alex; Joycelin Joycelin; Michelle Selvia Liu; Selvia Eka Marliana; Shelvi Shelvi; Hery Haryanto (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Inflation and unemployment are the most important performance descriptions in a country's macro economy, the difficulty in overcoming these two problems is not only experienced by developing countries, but also experienced by developed countries. The relationship between the inflation rate and the unemployment rate affects the mix of fiscal and monetary policy decisions of a country to achieve better economic conditions. The existence of a trade-off that occurs between inflation and unemployment is known as the Phillips Curve. However, an interesting phenomenon that often occurs in Indonesia is when the unemployment rate is high, the inflation rate is still high. This study aims to analyze the decision making of the provincial government of DKI Jakarta in terms of responding to the threat of an increase in the unemployment rate after the increase in the inflation rate by using time series data over a span of 5 years, starting from 2017-2021.